Family, Households and Women's Empowerment in Bahia, Brazil, Through the Generations: Continuities or Change? - Sardenberg, Cecília Maria Bacellar (2010)
This article identifies changes and continuities in gender relations in a working class neighbourhood in Salvador, Bahia, through the generations. Based on data collected over a period of nearly 20 years, it seeks to identify processes of women’s empowerment. It confirms the relevance of women’s economic independence to their participation in decision-making and in gaining autonomy; it gave them the power to assert control over their own lives. To this end, female solidarity has also played a special role, propitiating the exercise of power with to bring about the desired changes in one’s lives. However, neither economic independence nor female solidarity alone seems to have automatically led to conscious ‘gender rebellion’ and a break with traditional roles in the family. This only becomes possible when new values and attitudes in favour of alternative models, such as those proposed by contemporary feminisms, gain greater expression.